IMPLEMENTASI PEMBELAJARAN TEMATIK PADA SISWA SLOW LEARNER DI SEKOLAH INKLUSI - Nijma Aprilita; Habudin; Oman Farhurohman (STKIP Subang, 2024)
The aim of this research is to obtain a description of thematic learning applied to slow learner students in Inclusive Schools which includes planning, implementation and evaluation. This type of research is descriptive qualitative. Data collection techniques used include interviews, observation and documentation. The analysis method used has three stages, namely data reduction, data presentation and verification. The results of this research show that the implementation of thematic learning for slow learner students in inclusive schools is: 1) at the planning stage the activities include preparing learning tools such as academic calendars, program calendars for children with special needs, lesson plans, learning media, teaching modules, assessment plans for slow learner children . 2) at the implementation stage, the implementation of thematic learning for slow learner students in inclusive schools has gone well and adapted to the conditions that occur among slow learner students. 3) the learning evaluation stage in the class includes formative and summative assessments. The assessment given to slow learner students is different from others. The thematic learning given to slow learner students in inclusive schools has a positive impact. Slow learner students get the opportunity to study with their peers on various themes studied.